COMPARATIVE ANALYSIS OF LIVESTOCK INCOME PARTNERS THE BREEDER SELF IN THE DISTRICT DELI SERDANG - Muhammad Buchari Sibuea (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
ABSTRACTIn context farming activities of the people in Deli Serdang regency, especially poultry found two models of implementation that can be compare the effectiveness and efficiency, which is independent of livestock and livestock partner. In practice, more common people of independent farms, although with limitations, compared with cattle that generally supported partnering with strong funding and facilities of the partner companies. But it can not be denied, that although the company was providing facilities to farmers in partnership, the income of independent farmers is precisely at times better than the farmer partners. The results of this study clearly show that total revenue well above independent breeders partner. This paradoxical incident allegedly because independent farmers do not depend on the company partnership (in terms of policy and price), free to sell on the market and more cost-efficient production although acclaimed independent farmer must have more capital. It appears that the presence of the company partnered with the breeder people do not always provide satisfactory results in terms of both production and income. Therefore required a more in-depth understanding of all parties that partnership, so that in practice actually escorted such a way that can be run in accordance with the concept of partnership has been agreed previously. And for independent farmers are advised to absorb more current information about the farm a better and profitable (effective and efficient).Keywords: Farmer, income, partnership